Model of research management and level of the university research - Monteza Arbulú, César Augusto (2014)
The general objective was to validate a Management Model for research in the Faculty of Chemical Engineering and Food Industry at Pedro Ruiz Gallo National University, through expert judgment. This model seeks to improve the relevance of teachers‟ researching works and the graduates‟ thesis, to raise their applicability. It intends that researches should cover various scientific disciplines and their products should be innovative, that they can impact on the industry and able to be patented. The research was carried out in 2013, in the faculty of Chemical Engineering and Food Industries at Pedro Ruiz Gallo National University, Lambayeque. Prior to evaluate the Management Model for Research, it was essential to select people with experience in Management and Research, in order to confirm the real impact and the usefulness of the suggested model may have. The five selected experts for the validation of the model are university authorities or outgoing leaders, whose experiences contributed to the model. We proceeded to define the criteria used as benchmarks for experts responsible for this task and the scale of values for evaluation are established according to the importance that they represented. The Expert Judgment validated the proposed management model, and after their observations, they fully accepted the Model.